Dosimetry Evaluation of Treatment Planning Systems in Patient-Specific 3D Printed Anthropomorphic Phantom for Breast Cancer after Mastectomy using a Single-Beam 3D-CRT Technique for Megavoltage Electron Radiation Therapy - Endarko Endarko; Siti Aisyah; Aditya Prayugo Hariyanto; Mohammad Haekal; Nandia Kavilani; Ahmad Syafi’i (Journal of Biomedical Physics and Engineering, 2023)
Background: The patient-specific 3D printed anthropomorphic phantom is used for breast cancer after mastectomy developed by the laboratory of medical physics and biophysics, Department of Physics, Institut Teknologi Sepuluh Nopember, Indonesia. This phantom is applied to simulate and measure the radiation interactions occurring in the human body either using the treatment planning system (TPS) or direct measurement with external beam therapy (EBT) 3 film.Objective: This study aimed to provide dose measurements in the patient-specific 3D printed anthropomorphic phantom using a TPS and direct measurements using single-beam three-dimensional conformal radiation therapy (3DCRT) technique with electron energy of 6 MeV.Material and Methods: In this experimental study, the patient-specific 3D printed anthropomorphic phantom was used for post-mastectomy radiation therapy. TPS on the phantom was conducted using a 3D-CRT technique with RayPlan 9A software. The single-beam radiation was delivered to the phantom with an angle perpendicular to the breast plane at 337.3° at 6 MeV with a total prescribed dose of 5000 cGy/25 fractions with 200 cGy per fraction.Results: The doses at planning target volume (PTV) and right lung confirmed a non-significant difference both for TPS and direct measurement with P-values of 0.074 and 0.143, respectively. The dose at the spinal cord showed statistically significant differences with a P-value of 0.002. The result presented a similar skin dose value using either TPS or direct measurement. Conclusion: The patient-specific 3D printed anthropomorphic phantom for breast cancer after mastectomy on the right side has good potential as an alternative to the evaluation of dosimetry for radiation therapy.